Tropomyosin diffusion over actin subunits facilitates thin filament assembly - Fischer, Stefan; Rynkiewicz, Michael J.; Moore, Jeffrey R.; Lehman, William (Structural dynamics, 2016)
Coiled-coil tropomyosin binds to consecutive actin-subunits along actin-containing thin filaments. Tropomyosin molecules then polymerize head-to-tail to form cables that wrap helically around the filaments. Little is known about the assembly process that leads to continuous, gap-free tropomyosin cable formation. We propose that tropomyosin molecules diffuse over the actin-filament surface to connect head-to-tail to partners. This possibility is likely because (1) tropomyosin hovers loosely over the actin-filament, thus binding weakly to F-actin and (2) low energy-barriers provide tropomyosin freedom for 1D axial translation on F-actin. We consider that these unique features of the actin-tropomyosin interaction are the basis of tropomyosin cable formation.
Gesehen am 19.05.2020